-Non-Parametric Identification Of Generalized Hammerstein Models - Emara-Shabaik, Husam (2020)
The Hammerstein model is considered in a generalized form, where its nonlinearelement can have multi-inputs and a finite memory. The identification of the multiinput finite memory nonlinearity and the impulse response sequence of the model is treated using a non-parametric approach. A numerical example is given. The identification results of the example illustrate the effectiveness of the developed technique.